Western Evolutionism in the Muslim World (American Journal of Islam and Society, 1991)
As a general system of thought, evolutionism is the most powerful ideologyin modem Western secularist civilization. It arose in the West over a centuryago and spread there first, gradually reducing the Christian culture of theWest until it became a residual influence. Because Western nations such asEngland, France, and the Soviet Union imposed themselves on Muslim landsin the form of colonialist regimes, we should not be surprised to find withinthe Muslim world the echoes of evolutionary thdang in many of the modernist,or Westernized, Muslims, and even amongst their opponents, the Muslimfundamentalists. This was perhaps inevitable, given that the educational systemof the Muslim world has been patterned on that of the West.In the West, evolutionary modes of thought have gradually created asecularized world devoid of religious attachments. In the Muslim world, itis only natural that modernist Muslims, the so-called Westernized Muslimswho take their bearings from Western as opposed to Islamic thinking, shouldhave sought to create within Islam a similarly secularized culture, likewisecut off from its religious mots. Such Muslims have been the dominant influencein the Muslim world from the nineteenth century up to the Second WorldWar, ample time in which to realize their ambitions. In this fashion,evolutionism, an ideology that arose in the West and succeeded in utterlyde-Christianizing the West, has now penetrated into the Muslim world likea Trojan horse.That being so, we would do well to examine the origins of evolutionarythinking in the West to discern both its nature and to see how it displacedChristian beliefs and institutions. The secularist civilization it produced isnow sweeping the entire globe and threatening to destroy the lingering elementsof traditional Islamic civilization. By first examining what happened in theChristian world, we are in a better position to grasp what has been goingon within the domains of Islam in the recent past. That understanding shouldhave a direct bearing on the question of whether the traditional culture ofIslam can be preserved. Indeed, the world of Islam may very well be the ...